Identifying aflatoxin resistance related proteins/genes through proteomics and RNAi gene silencing - Chen, Z.Y.; Brown, R.L.; Guo, B.Z.; Menkir, A.; Cleveland, T.E. (American Peanut Research and Education Society, 2009)
Aflatoxins are carcinogenic secondary metab-olites produced mainly byAspergillus flavusLinkex. Fries, andA. prarasiticusSpeare duringinfection of susceptible crops, such as maize,cottonseed, peanuts and tree nuts. This paper willreview research efforts in identifying aflatoxinresistance-related proteins/genes in maize. Similarstrategies may be useful in peanut. For maize,although genotypes resistant toA. flavusinfectionor aflatoxin production have been identified, theincorporation of resistance into commercial lineshas been slow due to the lack of selectable markersand poor understanding of host resistance mech-anisms. Recently, resistance-associated proteins(RAPs) were identified through proteomic com-parison of constitutive protein profiles betweenresistant and susceptible maize genotypes. Theseproteins belong to three major groups based ontheir peptide sequence homologies: storage pro-teins, stress-related proteins, and antifungal pro-teins. Preliminary characterization of some ofthese RAPs suggest that they play a direct role inhost resistance, such as pathogenesis-relatedprotein 10 (PR10), or an indirect role, such asglyoxalase I (GLX I), through enhancing the hoststress tolerance. To verify whether these RAPsplay a role in host resistance, RNA interference(RNAi) gene silencing technique was used tosilence the expression of these genes in maize.RNAi vectors (glx IRNAi andpr10RNAi) wereconstructed using Gateway technology, and thentransformed into immature maize embryos usingboth bombardment andAgrobacteriuminfection.The extent of gene silencing in transgenic callustissues ranged from 20% to over 99%. The RNAisilenced transgenic maize seeds have also beenobtained from plants regenerated fromAgrobac-teriumtransformed callus lines. Kernel screenassay of the transgenic maize kernels demonstrat-ed a significant increase in susceptibility toA.flavuscolonization and aflatoxin production insome of the silenced transgenic lines comparedwith non-silenced control kernels, suggesting thedirect involvement of these two proteins inaflatoxin resistance in maize.